Effectiveness and Contribution of Local Taxes in Bengkulu Tengah Regency - Fellicia Triamanda; Abdullah Abdullah (Fakultas Ekonomi Dan Bisnis, Universitas Bengkulu, 2023)
The purpose of this study is to describe the condition of the effectiveness and contribution of local taxes and how the Regional Government of Bengkulu Tengah Regency increases the effectiveness and contribution of local taxes in the Bengkulu Tengah Regency. The type of research used in this study is a quantitative descriptive method using trend analysis. The trend analysis applied in this study uses the least square method (least square method) which will be used to calculate the projected local tax revenue in Bengkulu Tengah Regency for 5 years, 2021-2025. Based on the results of the analysis of the effectiveness of regional tax revenue as a whole in Bengkulu Tengah Regency in 2016-2020, it can be concluded that it has been very effective because the average level of effectiveness is above 100%. However, for each of the 11 types of local taxes, there are still ineffective ones that are ineffective because the effectiveness level is below 60%. Based on the analysis of the contribution of local tax revenues to the overall local revenue in Bengkulu Tengah Regency in 2016-2020 it can be concluded that the contribution of local taxes to local revenue is quite good and always increases every year. However, for each of the 11 types of local taxes, the contribution is still very low because the average contribution rate is below 10%. In meeting local tax targets, the Bengkulu Tengah Regency Government takes a collection and persuasive approach with taxpayers and always coordinates with related parties. If there is a decrease in the achievement of local tax targets, the Bengkulu Tengah Regency Government will evaluate and monitor directly in the field to find out the causes of the types of local taxes that have decreased. Based on the analysis of the trend of local tax revenues in Bengkulu Tengah Regency in 2021-2025 which has been carried out, the results of forecasting local tax revenues will always increase every year.